ANALISIS MINAT KONSUMEN DALAM MEMILIH RUMAH TYPE 54 PAUS FLOWER RESIDENCE DI PT EKAREDI MITRA NUSA PEKANBARU - Anita Vanty Feronika; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Interest is a form of such a person's attitude and sense of taste more like the attachment to a thing or activity without being told. This research was carried out in the Housing Paus Flower Recidence located street arwana.the purpose of reason authors conducted a study on this developer because PT.Ekaredi Mitra Nusa is a development company that has long build housing projects in Pekanbaru. In this research methodology is descriptive, where the samples used were residents of the type 54 of 60 respondents. To determine the sample using accidental sampling technique. The collection of data is through observation, interviews and questionnaires. From the analysis of consumer interest in choosing the type 54 into 8 sub variebel includes aspects of culture, social class aspect, the aspect of a small reference group, family aspects, aspects of the experience, personality, attitude and confidence and self-concept scores collected: 5407, which means 8 sub variables in interest in choosing a home type 54 Pope Flower Residence pertained agree. Keyword: analysis,consumer interest,type 54